(untitled) - Madura, Jeff (Australia, 2008)
This book describes financial markets and the financial institutions the serve those markets. It provides a conceptual framework that can be used to understand why markets exist. Each type of financial market is described, with a focus on the securiries that are traded in that market and the participation by financial institutions.
Keywords: Financial institutions,Capital market,Thể chế tài chính